A retrospective review of phyllodes tumours of the breast: A single institution experience. (April 2018) - Ganesh, Vithusha; Drost, Leah; Lee, Justin; Wan, Bo Angela; Zhang, Liying; Rakovitch, Eileen; Vesprini, Danny; Slodkowska, Elzbieta; Zeng, K. Liang; Sousa, Philomena; Yee, Caitlin; Lam, Henry; et al.
Abstract: Background: Phyllodes tumours are rare and histologically diverse, posing challenges in prognosis and treatment. Due to their rarity, they have seldom been studied. Purpose: The purpose was to investigate clinical practices in the management of phyllodes tumours, as well as patient outcomes to contribute to the limited body of knowledge surrounding these tumours. Methods: A retrospective review was conducted on all patients with phyllodes tumours at a single institution. Descriptive analyses were conducted on demographic, disease and treatment (breast-conserving surgery, mastectomy, surgical re-excision, adjuvant/palliative radiation, palliative chemotherapy) information. Overall and disease-free survivals were analyzed, and the cumulative incidence of recurrence and metastases was compared. Results: 79 patients with phyllodes tumours of the breast were included in the study. Tumours were classified as malignant, borderline, or benign in 67.1%, 21.5%, and 11.4% of patients, respectively. There were no statistically significant differences in overall or disease-free survival between patients with benign, borderline or malignant disease. Only patients with malignant disease developed recurrence or metastases. Those with malignant disease who received mastectomies had a lower 10-year cumulative incidence of recurrence; however this was not statistically significant (p = 0.69). All patients had negative surgical margins due to a re-excision or mastectomy following margin-positive breast conserving surgery. Of all risk factors assessed, necrosis was significantly associated with increased incidence of recurrence (local or distant) in patients with malignant disease (p = 0.03). Conclusion: The presence of tumour necrosis is a significant negative prognostic factor. Breast-conserving surgery may be adequate in providing local control, given negative surgical margins. Highlights: Phyllodes tumours are rare and diverse, posing challenges in prognosis and treatment. A single institution retrospective review was conducted. Tumor necrosis is a significant negative prognostic factor for malignant disease. Breast conserving surgery may be adequate for local control of malignant phyllodes tumours.